Common dolphins in the Gulf of Corinth are Critically Endangered. (9th November 2018) - Santostasi, Nina Luisa; Bonizzoni, Silvia; Gimenez, Olivier; Eddy, Lavinia; Bearzi, Giovanni
Abstract: Regional populations ("subpopulations") of globally abundant species can be exposed to human impacts that threaten their viability. Given the value of cetacean subpopulations as evolutionary significant units, keystone and umbrella species, it is important to assess their conservation status separately and propose area‐specific conservation measures. We used a threat assessment process and applied IUCN Red List criteria to a regional population of common dolphins Delphinus delphis in the semi‐enclosed Gulf of Corinth, Greece. We compiled subpopulation‐specific information about abundance and trends, estimated the geographic range of the subpopulation (area of occupancy and extent of occurrence), and calculated the probability of extinction through stochastic modelling. The subpopulation qualified as Endangered according to criteria A (population size reduction over three generations) and B (geographic range), and as Critically Endangered under criteria C (population size and decline) and D (very small or restricted population). The probability of extinction was estimated to be ≥50% in three generations, qualifying the subpopulation as Critically Endangered under criterion E (quantitative analysis). We concluded that the subpopulation should be classified as Critically Endangered. Considering the high extinction risk faced by common dolphins in the Gulf of Corinth, we recommend that: (a) immediate action is taken to mitigate anthropogenic activities known or suspected to have a negative impact on cetaceans in the area (particularly commercial fishing); and (b) a marine protected area is established in the Gulf of Corinth as a management tool for enforcing conservation action and facilitating the recovery of common dolphins.